Sosialisasi dan Pelatihan Ecoprint Sebagai Produk Kreatif bagi Masyarakat Desa Ngelo, Jatiroto, Wonogiri - Hery Widijanto; Intan R Al-Huda; Putu Elsa P Rahayu; Treza Daffa Ardy (JURNAL KARYA PENGABDIAN, 2023)
Ngelo Village is located in Jatiroto District, Wonogiri Regency, Central Java, where most of the population's income is dominated by the agricultural sector. The lack of skills and abilities of the people of Ngelo Village to manage the potential of existing natural resources is one of the problems in this village. Socialization and Training Activities for Making Ecoprint a Creative Product are one of the efforts to unravel existing problems. This activity aims to provide new insights into utilizing the potential of existing natural resources with ecoprint. In its implementation, it uses a participatory method, namely interactive learning activities with face-to-face learning. This activity includes an introduction to ecoprint, various ecoprint techniques, to the practice of making ecoprints on totebags. The results of the activity show the enthusiasm of the community in participating in socialization and their interest in making ecoprints. Participants can use ecoprint as an entrepreneurial potential and increase family income.